The tectonic development of the Central African Plateau: evidence from shear-wave splitting - Kounoudis, R; Kendall, J-M; Ogden, CS; Fishwick, S; Chifwepa, C; Daly, MC (Oxford University Press, 2024)
The Central African Plateau comprises a mosaic of numerous Archean terranes—the Congo, Bangweulu and Kalahari Cratons—sutured in a series of Proterozoic to early Cambrian orogenic events. Major upper-crustal deformation and complex craton margin fault zones reflect the region’s diverse tectonic history: rifting during the Neoproterozoic, collision during the Pan-African orogeny, and more recently, Permo-Triassic Karoo rifting and the Pliocene development of the Southwestern branch of the East African Rift. The tectonic evolution and extent to which the lithospheric mantle has been re-worked by each tectonic event is poorly understood. New seismograph networks across the Plateau provide fresh opportunity to place constraints on the plate-scale Precambrian-to-Phanerozoic processes that have acted across the region. Utilizing data from seismograph deployments across the Central African Plateau, including the new Copper Basin Exploration Science network—a NW–SE-trending, 750-km-long profile of 35 broad-band stations—we explore lithospheric deformation fabrics associated with past and present tectonic events via a shear-wave splitting study of mantle seismic anisotropy. Results reveal short length-scale variations in splitting parameters (fast direction: φ, delay time: δt), suggestive of a fossil lithospheric fabric cause for the observed anisotropy. A lack of fault-parallel φ across the Mwembeshi Shear Zone, suggests it may be too narrow at mantle depths, a thin-skinned, crustal-scale feature, and/or did not experience sufficient fault parallel shearstrain during its last active phase to form a lithospheric deformation fabric discernible via teleseismic shear-wave splitting. In the heart of the Lufilian Arc, we observe abrupt changes in splitting parameters with NE–SW, N–S and NW–SE φ and 0.5 s<δt<1.2 s evident at short length-scales: no single, uniform, anisotropic LPO fabric defines the entire region. This is consistent with the view that multiple episodes of deformation shaped the Lufilian Arc, or perhaps that pre-existing fabrics, relating to Neoproterozoic Katangan Basin development, have failed to be completely overprinted by the PanAfrican Orogeny. Near the Domes, where most intense crustal re-working is thought to have taken place during the Pan-African Orogeny, there is a cluster of null and low δt splits which likely reflects the lack of organised LPO fabrics, perhaps due to the presence of depth-dependent anisotropy. The neighbouring Congo Craton margin is marked by consistently weak anisotropy (δt<0.7 s) indicating a weak horizontal alignment of olivine at mantle lithospheric depths, typical of Archean terranes worldwide.